Aloe rubroviolacea Extracts: An Alternative Source for Potential Antimicrobials - Iqbal, Muhammad Naeem; Khalid, Tayyaba (PSM Biological Research, 2023)
Mostly antibiotics of microbial origin are used for the treatment of microbial infections. There have been reports of side effects for a few of these antibacterial substances. Excessive use can also develop antibiotic resistance conditions. Concerns about hygienic practices, the environment, regulations, and marketing have sparked a quest for natural plant-based antimicrobial agents as alternatives to some synthetic compounds to combat the current antibiotic resistance issues. The plant parts have been used for extraction of antimicrobial agents both in solid as well as in liquid form. In this issue, Ibrahim et al. (2023) report the antimicrobial activity of Aloe rubroviolacea extracts against some bacteria and fungi. Several plants have been investigated for their antibacterial properties, but new species may potentially present opportunities.